2013
DOI: 10.1128/jb.02291-12
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Analysis of the Planosporicin Lantibiotic Biosynthetic Gene Cluster of Planomonospora alba

Abstract: The increasing prevalence of antibiotic resistance in bacterial pathogens has renewed focus on natural products with antimicrobial properties. Lantibiotics are ribosomally synthesized peptide antibiotics that are posttranslationally modified to introduce (methyl)lanthionine bridges. Actinomycetes are renowned for their ability to produce a large variety of antibiotics, many with clinical applications, but are known to make only a few lantibiotics. One such compound is planosporicin produced by Planomonospora a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 55 publications
0
47
0
Order By: Relevance
“…RNA was extracted from mycelium harvested after 41, 73, 113, and 162 h. Culture supernatants from each time point were assayed for planosporicin production ( Fig. 2), which could be detected in M1304 and the wild-type strain after 41 and 162 h, respectively; M1302, M1303 and M1308 failed to produce the lantibiotic, as observed previously (25). Interestingly, M1304 (ΔpspW::oriT-hyg) exhibited precocious and increased levels of antibiotic activity compared with the wild-type strain (see later for further discussion).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…RNA was extracted from mycelium harvested after 41, 73, 113, and 162 h. Culture supernatants from each time point were assayed for planosporicin production ( Fig. 2), which could be detected in M1304 and the wild-type strain after 41 and 162 h, respectively; M1302, M1303 and M1308 failed to produce the lantibiotic, as observed previously (25). Interestingly, M1304 (ΔpspW::oriT-hyg) exhibited precocious and increased levels of antibiotic activity compared with the wild-type strain (see later for further discussion).…”
Section: Resultsmentioning
confidence: 99%
“…Previous RT-PCR studies (25) suggested that the psp gene cluster was transcribed in at least three operons, pspABCTUV, pspXWJYZQR, and pspEF. To identify the transcriptional start sites of these putative operons, and to assess whether pspR and pspJ, which are preceded by intergenic regions of 89 and 231 bp, respectively, were also transcribed from additional promoters, high-resolution nuclease S1 protection analyses were carried out using 32 P-5′ end-labeled probes complementary to the predicted 5′ ends of the transcripts of pspA, pspX, pspJ, pspE, and pspR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations